Kyai's Leadership Style in Forming the Independence of Santri - Chusnul Chotimah; Mohammad Febri Irawan Saputra (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This study discusses the Kyai's leadership style in improving the quality of Islamic education by forming independent students. Like those at Al-Falah Islamic Boarding School Bahrul Ulum Tambakberas Jombang, students at Al-Falah Islamic Boarding School in all aspects of needs within the scope of Islamic boarding schools, almost all of them are run by Santri independently. Therefore the author raises the theme